2009
DOI: 10.1534/genetics.108.100099
|View full text |Cite
|
Sign up to set email alerts
|

A Mutant Plasma Membrane Protein Is Stabilized Upon Loss of Yvh1, a Novel Ribosome Assembly Factor

Abstract: Pma1-10 is a mutant plasma membrane ATPase defective at the restrictive temperature in stability at the cell surface. At 37°, Pma1-10 is ubiquitinated and internalized from the plasma membrane for degradation in the vacuole. YVH1, encoding a tyrosine phosphatase, is a mutant suppressor of pma1-10 ; in the absence of Yvh1, Pma1-10 remains stable at the plasma membrane, thereby permitting cells to grow. The RING finger domain of Yvh1, but not its phosphatase domain, is required for removal of mutant Pma1-10 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 49 publications
5
21
0
Order By: Relevance
“…In yeast, the C-terminal zinc-binding domain is able to complement the slow-growth phenotype of a yvh1 deletion, 8,16 rescue the 60S export defect 12,13,16 and is necessary for glycogen accumulation, growth and spore maturation. 8 In humans, this domain can function as a redox sensor and is necessary for the cytoprotective function of hYVH1.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…In yeast, the C-terminal zinc-binding domain is able to complement the slow-growth phenotype of a yvh1 deletion, 8,16 rescue the 60S export defect 12,13,16 and is necessary for glycogen accumulation, growth and spore maturation. 8 In humans, this domain can function as a redox sensor and is necessary for the cytoprotective function of hYVH1.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…We observed that both wild-type hYVH1 and hYVH1 C115S (a phosphatase-inactive mutant) co-immunoprecipitated YB-1 and FMRP to a similar extent, suggesting that phosphatase activity is likely not required to associate with YB-1 and FMRP particles. Regarding the modular domains of hYVH1, the ZBD of hYVH1 has been shown to be required, and in some instances sufficient, for the observed hYVH1-mediated cellular functions, such as ribosome biogenesis (11)(12)(13), cell cycle regulation (14), and cell survival (15). As shown in Fig.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 98%
“…Although the precise physiological role of hYVH1 remains uncharacterized, recent evidence indicates that YVH1 orthologs may be critical mediators of ribosome biogenesis (11)(12)(13), cell cycle regulation (14), and cell survival (15,16). Furthermore, the hyvh1 gene has been found to be significantly amplified in various cancers that have progressed to advanced stages (17)(18)(19), highlighting the importance of examining the biological activities of hYVH1.…”
mentioning
confidence: 99%
“…Defects within specific steps or association of proteins with defined complexes within this multistep process can be inferred from polysome analyses as each complex in endowed with a unique sedimentation coefficient within sucrose gradients [80]. Polysome analysis in yeast demonstrated that Yvh1p associates with pre-60S ribosomes and loss of YVH1 results in an increase in half-mers (consisting of a 48S small subunit that fails to join to a large 60S ribosomal subunit) [81]. The production of translationally incompetent half-mers likely results from defects in cytoplasmic 60S maturation [80,81].…”
Section: Dusp12mentioning
confidence: 99%
“…Polysome analysis in yeast demonstrated that Yvh1p associates with pre-60S ribosomes and loss of YVH1 results in an increase in half-mers (consisting of a 48S small subunit that fails to join to a large 60S ribosomal subunit) [81]. The production of translationally incompetent half-mers likely results from defects in cytoplasmic 60S maturation [80,81]. In addition to specific temporal associations of initiation factors with the 40S subunit, the nuclear pre-60S subunits associate with Mrt4p, which is subsequently displaced by the P0/P1/P2 ribosomal stalk proteins upon export of the complex into the cytoplasm [78,82].…”
Section: Dusp12mentioning
confidence: 99%